A hyperplastic anterior choroidal artery with double persistent anastomotic channels. - Chen, C J; Barkovich, A J (American Journal of Neuroradiology, 1998)
We describe a case of a hyperplastic anterior choroidal artery (AChA) with double persistent anastomotic channels. This hyperplastic AChA, which was detected at vertebral angiography, is different from previously reported cases, because it has an unusual, secondary anastomotic channel.